Means substitutability in personal significance restoration - Contu, Federico; Ellenberg, Molly; Kruglanski, Arie W.; Pierro, Antonio (Frontiers in Psychology, 2023)
Drawing on Significance Quest Theory, we hypothesized that when people experience a loss of significance related to a specific life domain, they will aim to restore their significance by acting in an extreme manner in a different life domain. To test this hypothesis, we ran two cross-sectional studies using samples of employed people in romantic relationships. Study 1 tested if people experiencing a loss of significance in the romantic relationship domain were more prone to extremism at work. Study 2 tested whether people experiencing work-related significance loss were more prone to engage in obsessive relational intrusion (ORI) toward their romantic partner. Results from both studies confirmed our hypothesis, suggesting that both amorous relationships and careers are perceived as fruitful in maintaining or restoring ones’ sense of personal significance, even if the original loss of significance is derived from an unrelated domain. Notably, this research represents one of the first tests of the key assumption of Significance Quest Theory entailing the substitutability of means through which one can attain or renew their sense of significance.